Dekonstruksi Makna Hubungan Beracun: Analisis Semiotika Saussurean terhadap Narasi Toxic Relationship dalam Film Bucin - Mukhamad Dafa Asadin; Khusnul Khotimah (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
A toxic relationship is a relationship that makes one or both parties feel unloved, do not receive support, are always put down, misunderstood, or attacked emotionally or physically. The issue of Toxic Relationships is that many films have appeared that address this case. One of them is the film Bucin. The film Bucin is a film written by Jovial Da Lopez and directed by Chandra Liow. This research will examine the representation of toxic relationships in the film Bucin using Ferdinand De Saussure's semiotic model. From the results of the analysis carried out, it was found that the Bucin film represents a toxic relationship in several scenes. The toxic relationship represented in the film Bucin is packaged in various situations and has different signs of a toxic relationship. Scene 1 shows signs of a toxic relationship in the form of not being able to be yourself, scene 2 shows signs of a toxic relationship in the form of always being controlled by your partner and often lying, and scene 3 shows signs of a toxic relationship in the form of frequent lying and lack of support.